2010
DOI: 10.1038/nprot.2010.11
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, cultivation and characterization of adult murine prostate stem cells

Abstract: ABSTRACT/SUMMARY The successful isolation and cultivation of prostate stem cells will allow us to study their unique biological properties and their application in therapeutic approaches. Here we provide step-by-step procedures on the basis of previous work in our laboratory for: the harvesting of primary prostate cells from adolescent male mice by a modified enzymatic procedure; the isolation of an enriched population of prostate stem cells through cell sorting; the cultivation of prostate stem cells in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
222
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(228 citation statements)
references
References 18 publications
6
222
0
Order By: Relevance
“…Most importantly, the finding that cells of origin of prostate cancer reside in the basal compartment is consistent with findings in human and murine tissues by Witte and coinvestigators who used high expression of Trop2 and CD49f to enrich for prostatic basal cells [3,4,33]. In addition to this, Wang et al showed luminal stem cells (CARNs) are also a cell of origin of prostate cancer in mouse prostate [1].…”
Section: Discussionsupporting
confidence: 71%
“…Most importantly, the finding that cells of origin of prostate cancer reside in the basal compartment is consistent with findings in human and murine tissues by Witte and coinvestigators who used high expression of Trop2 and CD49f to enrich for prostatic basal cells [3,4,33]. In addition to this, Wang et al showed luminal stem cells (CARNs) are also a cell of origin of prostate cancer in mouse prostate [1].…”
Section: Discussionsupporting
confidence: 71%
“…Before performing the coinjections, UGSM was prepared freshly from foetuses of E16 C57Bl/6 mice as previously described by Lukacs et al . 6. Briefly, timed pregnancies of C57/BL6 mice were set up and pregnant females were killed at day 16 (E16).…”
Section: Methodsmentioning
confidence: 99%
“…CK8 expression was not observed in WT and Abcg2 null spheres at day 14 using immunofluorescence staining. Previous studies document inability to detect high CK8 protein expression in spheres before day 14 [31]. Dual immunofluorescence staining of p63 and CK5 showed heterogeneity in terms of colocalization of p63 and CK5.…”
Section: Fig 3 Sphere Formation Efficiency Is Increased With Enhancmentioning
confidence: 99%
“…2B). The sphere formation efficiency determines in vitro proliferation and differentiation potential of basal and stem/progenitor cells [31]. Although the number of p63 expressing basal cells was not changed after one and five cycles of regression and regeneration (Fig.…”
Section: Luminal Cell Number Is Decreased In Abcg2 Null Ventral Prostmentioning
confidence: 99%
See 1 more Smart Citation